A cryptographic framework for secure medical imaging in smart healthcare environments - Kusum Lata; Chitraksh Gupta; Linga Reddy Cenkeramaddi (Results in Engineering)
In the dynamic environment of innovative healthcare, securing medical images is indispensable because they are commonly sent and stored over digital media. This paper introduces a strong hybrid encryption scheme combining AES-128 (Advanced Encryption Standard) and RSA-1024 (Rivest-Shamir-Adleman) to improve security and the performance of medical image encryption. The new model employs AES-128 to encrypt images speedily and efficiently and RSA-1024 to securely share keys. Experimental verification was performed on a brain MRI dataset of 7023 images of 512 × 512 pixels. Encryption time ranged from 0.5 to 2.9 seconds depending on the AES mode, whereas decryption was significantly faster, from 0.1 to 0.9 seconds. The throughput analysis indicated encryption rates of up to 21.8 Mbps and decryption rates of 22.5 Mbps, with the best performance in CTR and OCB modes. Security was measured with MSE, PSNR, NPCR, UACI, histogram uniformity, correlation analysis, and entropy. PSNR was more than 50 dB in CFB and CBC modes, NPCR was more than 99.5 %, and entropy was close to the ideal value of 8 in encrypted images. The findings validate that the hybrid AES-RSA scheme attains an optimal level of confidentiality without loss of computational efficiency, and it is thus fit for real-time and secure medical image processing applications in contemporary healthcare systems.